CIVILIZATION AND THE DIGITAL ERA Opportunities and Challenges for the World and Indonesia - Alwi Alatas (Qurthuba: The Journal of History and Islamic Civilization, 2023)
Abstract: This article examines the meaning and development of civilization and relates it to today's digital era, using particularly Islamic view. Society has evolved over several millennia, from small wandering communities to complex urban settlements. The population grew, a number of innovations were produced, and societies extended into civilizations. Civilizations emerge and decline, while sciences continue to grow and become more advanced throughout history. In the last few decades, the world has entered the digital era with very fast innovation and progress. Technological changes affect the way humans think, work, and behave. Digital technologies open up a number of opportunities, but also creates new challenges, including for Indonesia. Among the important challenges underlined by this research is the distraction and reduction of spiritual values and the essence of humanity, which are at the core of civilization according to Islamic perspective. It is a civilizational responsibility for today’s society to make sure that digital development will not reduce humanity and will not distract it from moral-spiritual values and objectives. Keywords: Civilization, digital era, Indonesia, Islam, spirituality, technology